C.4 Epigenetic drivers of malignant transformation in diffuse gliomas. (November 2021) - Voisin, MR; Patil, V; Nassiri, F; Zadeh, G
Abstract : Background: Despite treatment, gliomas often exhibit disease progression, leading to recurrent glioblastoma (GBM) or malignant transformation of low-grade gliomas (LGG) associated with treatment resistance and poor prognosis. To date, the molecular factors driving glioma recurrence are poorly understood. Methods: We analyzed a cohort of 324 glioma samples from our institution including a unique cohort of 81 patients with matched primary and recurrent tumour pairs. We performed a paired, integrated multi-platform analysis consisting of DNA methylation profiling on all 324 samples, gene expression on 87 samples, and matched plasma cell-free DNA methylome analysis on 82 samples. Results: LGG that undergo malignant transformation are associated with DNA hypomethylation at recurrence, including decreased tumour purity and increased copy number variation. Integrated pathway analyses identified IL-6, associated with multiple pro-oncogenic pathways, and CCR2, associated with the recruitment of tumour-associated macrophages, as top genes involved in malignant transformation. Matched plasma methylation demonstrated a shift in the methylation signature at recurrence that can prove valuable as a non-invasive biomarker for early detection of malignant progression. Conclusions: We provide the first detailed description of the epigenetic evolution of gliomas and identify epigenetic drivers of malignant transformation including non-invasive biomarkers for early detection of malignant progression.